2007
DOI: 10.1074/jbc.m609388200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cell-permeable Antioxidant Peptide, SS31, Attenuates Ischemic Brain Injury by Down-regulating CD36

Abstract: Oxidative stress is implicated in the pathogenesis of ischemia/ reperfusion injury. Recently, we demonstrated that activation of CD36, a class B scavenger receptor, mediates free radical production and tissue injury in cerebral ischemia (1). Oxidized low density lipoproteins (oxLDL) are among the ligands that bind to CD36 and are elevated in acute cerebral infarction. SS31 is a cell-permeable antioxidant peptide that reduces intracellular free radicals and inhibits LDL oxidation/lipid peroxidation (2). The cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
128
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(134 citation statements)
references
References 47 publications
4
128
1
1
Order By: Relevance
“…Consistent with this, we have reported that inflammatory corneal neovascularization induces elevated levels of CD36 (18), whereas others have documented an up-regulation of CD36 during cerebral ischemia (29) and an attenuation of its expression and activity following antioxidant treatment (30,31). Collectively, these studies led us to hypothesize that hypoxia modulates CD36 expression and function, with the objective of characterizing the mechanisms behind its regulation.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Consistent with this, we have reported that inflammatory corneal neovascularization induces elevated levels of CD36 (18), whereas others have documented an up-regulation of CD36 during cerebral ischemia (29) and an attenuation of its expression and activity following antioxidant treatment (30,31). Collectively, these studies led us to hypothesize that hypoxia modulates CD36 expression and function, with the objective of characterizing the mechanisms behind its regulation.…”
supporting
confidence: 53%
“…Transcripts-Studies have demonstrated that ROS generated during cerebral ischemia are markedly attenuated in Cd36 null mice and that treatment with antioxidant peptides down-regulates ischemia-induced CD36 expression (29,31). Consequently, we sought to determine whether ROS activity was implicated in the hypoxic regulation of CD36.…”
Section: Ros Are Involved In the Hypoxic Induction Of Cd36mentioning
confidence: 99%
“…No function for CD36 has been identified, however, on VSMCs. Since FeCl 3 and other injuries induce thrombosis via generation of oxidant damage and since CD36 has been reported to promote ROS formation in macrophages in vitro and in a murine cerebral ischemia model in vivo (13,14), we hypothesized that CD36 on VSMCs could contribute to vascular injury by generating further oxidant stress and that part of the "thrombo-protection" seen in cd36 -/-mice is due to diminished ROS production in the vessel wall.…”
Section: Introductionmentioning
confidence: 99%
“…3,4) Besides, operations have some strict indications and risk. 5 7) Many pharmacological interventions such as cerebral vasodilator, 8) thrombolytics, 9) Ca 2+ channel blocker, 10) antioxidant 11) and free radical scavenger 12) have been observed to produce acute ischemia and cerebral ischemia-reperfusion protection. Meanwhile, we still have to face that these medications present various problems such as serious side eŠects, uncertain curative eŠects, low compliance even toxicity.…”
Section: Introductionmentioning
confidence: 99%